(untitled) (Revista Tópos, 2013)
Este artigo discute a postura política que estava em jogo na opção pelo uso do concreto armado em construções, bem como alguns dos pressupostos arquitetônicos do arquiteto Vilanova Artigas. Uma construção que se faz pelos embates da chamada “arquitetura paulista” em relação à “arquitetura carioca” e pela análise crítica da casa Olga Baeta e da casa Rubem de Mendonça. Palavras-chave: Arquitetura Moderna, Arquitetura paulista, Projeto. PAULISTA ARCHITECTURE: THE POLITIC POSTURE IN OPITION FOR REINFORCED CONCRETE FROM TWO WORKS OF VILANOVA ARTIGAS ARCHITECT Abstract This article discusses the posture policy that was at stake in the option for the use of ferroconcrete, as well as some of the architectural assumptions of the architect Vilanova Artigas. A construction which is by conflicts "architecture paulista" in relation to "architecture carioca" and the critical analysis of the house Olga Baeta and of the house Rubem de Mendonça. Keywords: Modern Architecture, paulista architecture, Project.